E-MODULE DEVELOPMENT IN ELECTRICAL CIRCUITS COURSES BASED ON PROJECT LEARNING - Mahendra, I Gede Budi; Ticoh, Janne Deivy; Olii, Djami; Nursusanto, Usman (DPTE FT UNY, 2023)
The lack of maximum learning motivation has a direct impact on student lecture out-comes. The provision of teaching modules needs to be adjusted to ICT developments in order to provide more meaningful lectures. This development research aims to produce e-modules based on project learning (PjBL) in electrical circuit courses that are valid, practi-cal and have a positive impact on student learning outcomes. This research is development research using the ADDIE model with five stages: analysis, design, development, imple-mentation, and evaluation. The subjects of this study consisted of 2 material, media, lan-guage experts, 38 semester 2 students, and 2 course lecturers. Data was collected through questionnaires and tests. The research instruments included validity and practicality ques-tionnaire sheets, as well as tests of electrical circuit lecture results. The results of the re-search show that the E-module developed has a validity level from media experts of 90.00% with a Very Valid classification, a validity level from language experts of 86.00% with a Very Valid classification, and a validity level from material experts of 92.00 % with Very Valid classification. This PjBL-based e-module also has a level of practicality in terms of the student aspect of 88.14%, including in the